2017
DOI: 10.1038/srep40822
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor expression on von Hippel-Lindau-associated hemangioblastomas offers novel therapeutic target

Abstract: Von Hippel-Lindau (VHL)-associated hemangioblastomas (VHL-HB) arise in the central nervous system (CNS), and are a leading cause of morbidity and mortality in VHL disease. Currently, surgical resection is the most effective way to manage symptomatic VHL-HBs. Surgically unresectable VHLHBs or those in frail patients are challenging problems. Therapies targeting oncologic and vascular endothelial growth factor (VEGF) pathways have failed to demonstrate tumor control. Our experience and previous reports on VHL-HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…HB tumor cells were isolated as previously described. 24,30 Briefly, isolated HB cells were incubated at 37°C for 24 hours after isolation in DMEM supplemented with 10% fetal bovine serum, l-glutamine, penicillin, streptomycin, and F-12K. All subsequent experiments were performed within 24-48 hours of HB extraction.…”
Section: Hb Stromal Cell Extraction and Cell Culturementioning
confidence: 99%
“…HB tumor cells were isolated as previously described. 24,30 Briefly, isolated HB cells were incubated at 37°C for 24 hours after isolation in DMEM supplemented with 10% fetal bovine serum, l-glutamine, penicillin, streptomycin, and F-12K. All subsequent experiments were performed within 24-48 hours of HB extraction.…”
Section: Hb Stromal Cell Extraction and Cell Culturementioning
confidence: 99%
“…The accuracy of this method is based on the molecular characteristics of tumoral cells and especially somatostatin receptors overexpression by hemangioblastomas. Sizdahkhani et al recently demonstrated that surgically resected hemangioblastomas express different SSTR subtypes (1, 2a, 4, and 5) [10]. Hemangioblastomas may appear anywhere along the neuraxis, but sacral hemangioblastoma is less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorodeoxyglucose-positron emission tomography (PET-FDG) can be particularly helpful in finding PNETs smaller than 1 cm in diameter or in visualising small hepatic metastases that cannot yet be seen in classic contrast-enhanced CT scans. Added to this, in certain situations, PET-FDG, unlike classic CT, may help to differentiate serous pancreatic adenomas from PNETs, thus helping to decide whether to operate the patient or not [10,32,33].…”
Section: Reviewmentioning
confidence: 99%